Delayed recurrence of complete atrioventricular block following ablation for premature ventricular complexes - Yao Zhao; Xueyan Ding; Jiang Cao; Xinmiao Huang (Journal of Cardiothoracic Surgery)
Abstract A 77-year-old man was admitted for catheter ablation due to frequent premature ventricular complexes (PVCs). Activation mapping revealed that the earliest ventricular activation during the PVC was recorded on the left upper septum, where a clear His bundle electrogram was recorded during sinus rhythm. Radiofrequency ablation was performed with step-wise incremental application of the radio frequency energy. AV block was observed twice during RF ablation and disappeared within 5 s after stopping energy application each time. As he exhibited normal atrioventricular conduction, the patient was discharged home the following day. Five days after discharge, he experienced recurrent syncope, with ECG showing complete heart block. Although continuous telemetric echocardiogram monitoring revealed resolution of the complete atrioventricular block after 8 days, it recurred 5 days after. Follow-up evaluation of the pacemaker revealed persistent atrioventricular block at 3 and 6 months.